2017
DOI: 10.1051/ocl/2017048
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oils fromDuranta repensleaf and seed

Abstract: -The knowledge of the chemical composition of unpopular sources of edible oils has become paramount to supplement the usage of widely known vegetable oils. In this study, the gas chromatographic quantification of fatty acids and phytochemicals was carried out, and the physicochemical and micronutrient composition of Duranta repens leaf and seed oil were evaluated using standard methods. The leaf oils contained significantly higher (p < 0.05) peroxide, iodine and thiobarbituric acid values, refractive index, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 32 publications
2
19
4
Order By: Relevance
“…The acid values in this study were higher than the acid value for raw, sun-dried and roasted groundnut oil (2.35, 1.79 and 2.52 mgKOH/g respectively) as reported by Ayoola and Adeyeye [21]. It was however, lower than that found in Duranta repens seed oil (21.01 mgKOH/g) as reported by Agomuo et al [10] and plukeneti aconophora (11.5mg KOH/g) as shown by Akintayo and Bayer [22]. The low acid values of the raw, boiled and fermented seeds of HS (2.51, 4.02 and 4.66 mgKOH/g respectively) strongly suggest that the oil may be very suitable for manufacture of soap, cooking, manufacture of margarine, mayonnaise, salad oils and cosmetics.…”
Section: Physicochemical Propertiescontrasting
confidence: 73%
See 2 more Smart Citations
“…The acid values in this study were higher than the acid value for raw, sun-dried and roasted groundnut oil (2.35, 1.79 and 2.52 mgKOH/g respectively) as reported by Ayoola and Adeyeye [21]. It was however, lower than that found in Duranta repens seed oil (21.01 mgKOH/g) as reported by Agomuo et al [10] and plukeneti aconophora (11.5mg KOH/g) as shown by Akintayo and Bayer [22]. The low acid values of the raw, boiled and fermented seeds of HS (2.51, 4.02 and 4.66 mgKOH/g respectively) strongly suggest that the oil may be very suitable for manufacture of soap, cooking, manufacture of margarine, mayonnaise, salad oils and cosmetics.…”
Section: Physicochemical Propertiescontrasting
confidence: 73%
“…The low levels of percentage FFA in the three samples (1.26, 2.01 and 2.05% respectively) indicate that the oils from them may be useful edible oils that may be stored for a long time without spoilage via oxidative rancidity. The peroxide value of the samples were higher than that reported for water melon seed (3.24 mleq/kg) by Gladvin et al [25] and different refined groundnut species (1.30 -1.73 mleq/kg) by Nkafamiya et al [26] but lower than those of Opuntia dilleni (15.60 mleq/kg) by Njoku et al [27], crude groundnut oils (22.06 -25.03 mleq/Kg) [26], Duranta repens leaf oil (20.00 mleq/kg) and Duranta repens seed oil (12.29 mleq/kg) by Agomuo et al [10]. The peroxide values of the samples of Hibiscus sabdariffa seeds increased possibly as a result of boiling and fermentation.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fat contents of the eggplant in this study compared with those of leafy vegetables (Udosen, 1995), while the result of this study further indicated that the eggplant is a better carbohydrate source when compared to those for its fruit varieties; S. aethiopicum and S. macrocarpum (Nwodo et al, 2011). Ribalinidine and lunamarine are recognized alkaloids with antimalarial and analgesic effects (Agomuo et al, 2017), hence, the eggplant stalk could potentially possess effective antimalarial and analgesic properties.…”
Section: Resultsmentioning
confidence: 99%
“…The higher measurements of the characteristics reported for the crude oils revealed the necessity to purify the oils. In addition, the high values of oil RI also showed that the oil samples contain long chain fatty acids with a large number of carbon atoms (Bello and Olawore, 2012;Agomuo et al, 2017).…”
Section: Refractive Indexmentioning
confidence: 99%